A method of in-situ monitoring multiple parameters and blade condition of turbomachinery by using a single acoustic pressure sensor. (1st July 2022) - Zhang, Jingqi; Li, Ning; Chen, Yugang; Zhai, Jingyu; Han, Qingkai; Hou, Zengxuan
Highlights: Dynamic acoustic pressure measurement is proposed to obtain information for rotation speed, temperature and blade tip clearance. The standing wave method is adopted to measure the temperature, the calculation formula of tip clearance based on the acoustic attenuation model is deduced, and the blade wear loss is inferred from the amplitude of corresponding time-domain response. The accuracy and effectiveness of the proposed method are verified by the fan test-bed with 7 blades. Abstract: In this paper, a method of using a single acoustic pressure sensor to evaluate multiple physical parameters (pressure, rotation speed, temperature) of the turbomachinery and monitor the condition of rotating blades in-situ through the interpretation of dynamic acoustic pressure generated by the rotating components is proposed. The time-domain response of dynamic acoustic pressure is transformed by Fast Fourier Transform (FFT) to obtain the rotation frequency of the blade and calculate the rotation speed of turbomachinery, the standing wave method is adopted to measure the temperature of the rotating equipment synchronously with the dynamic acoustic pressure. Furthermore, the formula for calculating the distance between the rotating blade tip and the case based on the acoustic attenuation model is derived, which can demonstrate the change of blade tip clearance, even blade wear, and fracture. Finally, a fan test-bed with seven blades is built for test verification, the results show that the rotation speed and temperature measured based on dynamic acoustic pressure are consistent with the measured results of commercial instruments, and it is also effective and accurate to measure the change of tip clearance and predict the wear and fracture of blade through the time-domain response of dynamic acoustic pressure. Therefore, in-situ dynamic acoustic pressure measurement with a single sensor is a promising method that can be used for both parameter evaluation and condition monitoring of turbomachinery.